2015
DOI: 10.1140/epjc/s10052-015-3670-8
|View full text |Cite
|
Sign up to set email alerts
|

Aharonov–Bohm phase for an electromagnetic wave background

Abstract: The canonical Aharonov-Bohm effect is usually studied with time-independent potentials. In this work, we investigate the Aharonov-Bohm phase acquired by a charged particle moving in time-dependent potentials. In particular, we focus on the case of a charged particle moving in the time-varying field of a plane electromagnetic wave. We work out the Aharonov-Bohm phase using both the potential (i.e. A μ dx μ ) and the field (i.e. 1 2 F μν dσ μν ) forms of the Aharonov-Bohm phase. We give conditions in terms of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 22 publications
3
16
0
Order By: Relevance
“…We see that this result agrees with the spacetime line integral of the 4-vector potential from (16) or (17). Thus we find that, for this case, the time-dependent 4D version of Stokes' theorem is satisfied.…”
Section: The Infinite Time-dependent Solenoidsupporting
confidence: 84%
See 1 more Smart Citation
“…We see that this result agrees with the spacetime line integral of the 4-vector potential from (16) or (17). Thus we find that, for this case, the time-dependent 4D version of Stokes' theorem is satisfied.…”
Section: The Infinite Time-dependent Solenoidsupporting
confidence: 84%
“…(3) does not have a well known right hand rule as is the case for purely spatial contours and areas. The directionality that we have chosen above for the spacetime area is taken so that the area integral of the fields in (18) agrees with the results of the contour integrals of the two vector potentials given in (16) and (17) for the closed contour given in Fig. (2) (i.e.…”
Section: Appendix IIImentioning
confidence: 77%
“…We would also comment on our calculation and result in relation to two other relevant investigations of ABE II. Bright et al [18] have investigated time dependent ABE II wherein the time dependence of the fields comes from an electromagnetic wave background. The cancellation of the electric and magnetic fringe shifts was shown to be approximate.…”
Section: Discussionmentioning
confidence: 99%
“…(3) are taken into account. It has been shown that as long as the charging rate of the magnetic field is considerably larger than the typical scale of the particle traveling between the source and screen, there is no net phase shift in the time-dependent Aharonove-Bohm effects [31,32,33,34,35,36]. Therefore the time-dependent AB effect can be employed to investigate tiny derivation from zero in the phase shift which is induced by unknown new physics at high energy scale.…”
Section: Introductionmentioning
confidence: 99%